Factors of regional distribution of banking institutions in Russia - Anna Mishura; Svetlana Ageeva (European Regional Science Association (ERSA), 2016)
The article presents results of research into territorial disparity of bank (branch) deployment for regions of Russia. It is suggested that there have been three periods of bank development in the country. The Siberian Federal District has been selected to illustrate each period and demonstrate real institutional changes of power distribution between the 'province' and the 'center' as well as the role of the state throughout the process. The dynamics of the number of regional banking institutions in recent years reflects falling concentration of banking business in all regions (with the exception of Moscow). However, despite the concentration of financial institutions in the capital there are notable regional financial centers. It has been attempted to identify factors for the territorial disparity. It turns out that beside regional population and income size significant factors include the status of the regional capital city and its educational potential.
Keywords: R12; R51; G21; 330; Regional disparity; Capital city; Banking institutions